Noble Character Education Management to Improve Students’ Concern for the Learning Environment - Mustakim Mustakim; Eva Dianawati Wasliman (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2026)
This study aims to describe and analyze the management of noble character education to improve students’ concern for the learning environment at SDN Tegallega and SDN Jatinagara in Sindangbarang District, Cianjur Regency. This research used a qualitative approach with a multiple case study design. The analysis was based on Terry’s management functions, including planning, organizing, actuating, and controlling, and Mulyasa’s character education approach, which emphasizes value integration, habituation, teacher role modeling, and family involvement. Data were collected through observation, in-depth interviews, and documentation involving school principals, teachers, students, and parents. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings show that noble character education management was implemented through lesson plan integration, classroom routines, school cleanliness programs, teacher supervision, student duty schedules, daily habituation, behavior monitoring, and parent communication. SDN Tegallega demonstrated stronger program-based management through lesson plan integration, Friday Clean activities, and routine classroom inspections, while SDN Jatinagara demonstrated stronger culture-based management through religious routines, persuasive guidance, individual behavior journals, and parent communication. Supporting factors included teacher role modeling, school habituation, student participation, and principal supervision. In contrast, inhibiting factors included limited facilities, inconsistent student awareness, teacher workload, heterogeneous student backgrounds, and limited parental involvement. This study concludes that noble character education can improve students’ concern for the learning environment when systematically managed, consistently implemented, and collaboratively supported.